VIOLETA DINESCU UND DER SCHLÜSSEL DER TRÄUME. JUBILÄUMS-PORTRÄT - Bianca ŢIPLEA TEMEŞ (Studia Universitatis Babeş-Bolyai. Musica)
Fusing together in her artistic background two utterly contrasting worlds such as Romania and Germany, the composer Violeta Dinescu succeded to achieve a unique, distinctive voice in contemporary composition. By means of this dialogue, celebrating the musician’s 60th anniversary, her portrait will be reconstructed in its multiple components: the composition, the teaching activity as well as her unceasing effort of bringing Romanian culture at the forefront of the international artistic life. Although the article is entirely devoted to Violeta Dinescu’s celebration, using a Borgesian key to access her musical universe, the name of Dinescu’s composition teacher in Bucharest, Myriam Marbe, is often mentioned, marking a pedal point of this dialogue.